A method for the unbiased and efficient segmental labelling of RNA-binding proteins for structure and biophysics. Issue 1 (December 2017) - Gallagher, Christopher; Burlina, Fabienne; Offer, John; Ramos, Andres
Abstract Most eukaryotic RNA regulators recognise their RNA and protein partners by the combinatorial use of several RNA binding domains. Inter-domain dynamics and interactions play a key role in recognition and can be analysed by techniques such as NMR or FRET, provided that the information relative to the individual interactions can be de-convoluted. Segmentally labelling the proteins by ligating labelled and unlabelled peptide chains allows one to filter out unwanted information and observe the labelled moieties only. Several strategies have been implemented to ligate two protein fragments, but multiple ligations, which are necessary to segmentally label proteins of more than two domains, are more challenging and often dependent on the structure and solubility of the domains. Here we report a method to ligate multiple protein segments that allows the fast, high yield labelling of both internal and end domains, depending on the requirements. We use TCEP and mercaptophenylacetic acid (MPAA) in an optimised reaction environment to achieve an efficient ligation of protein domains independently from their structure or solubility. We expect the method will provide a useful tool for the molecular study of combinatorial protein–RNA recognition in RNA regulation.